Emlékmisék, királymisék Kunszentmártonban - Barna Gábor; „A királyhűség jól bevált útján...” Rendi és nemzeti kötődések szimbolikus változásai 1867 és 1918 között (2014) (Szeged) (2016)
Surviving documents in the archive of the Saint Martin Parish of Kunszentmárton (Jász-Nagykun-Szolnok County, up to 1993 Eger Archdiocese, since then Szeged-Csanád Diocese) provide information on the central wishes and rules, ideals and thoughts that shaped the annual order of feasts around the turn of the previous century. The result shaped the local structure of feasts in the market town of Kunszentmárton at the turn of the century. Three-fold main thread of the festive order:1. memorial days, feasts related to the royal house and events in the life of the royal family (birthdays, name days, coronation anniversary, deaths and anniversaries of deaths), that is, a feudal, dynastic thread,2. major feasts of the Catholic church, that is, the ecclesiastical thread (major feasts, anniversaries of priests/bishops, papal election)3. anniversaries of the events of 1848/49, commemorations linked to outstanding Hungarian figures, that is, the Hungarian national, bourgeois national idea.The three threads coexisted peacefully. The parish priest invited to the memorial masses the municipal/local authority, the state bodies, from the 1890s and to certain events also the civil associations. The established order of feasts was the following:- 30th March: “high masses for the defenders of the homeland” (at this date from 1868, before that in November)- 11th April: anniversary of the adoption of the laws of 1848, national feast - Easter, movable feast- 8th August: birthday of the king, Francis Joseph- 10th September: memorial day of the murder of Queen Elisabeth (from 1899)- 4th October: name day of the king, Francis Joseph 277BARNA GÁBORMEMORIAL MASSES, ROYAL MASSES IN KUNSZENTMÁRTONSurviving documents in the archive of the Saint Martin Parish of Kunszentmárton (Jász-Nagykun-Szolnok County, up to 1993 Eger Archdiocese, since then Szeged-Csanád Diocese) provide information on the central wishes and rules, ideals and thoughts that shaped the annual order of feasts around the turn of the previous century. The result shaped the local structure of feasts in the market town of Kunszentmárton at the turn of the century. Three-fold main thread of the festive order:1. memorial days, feasts related to the royal house and events in the life of the royal family (birthdays, name days, coronation anniversary, deaths and anniversaries of deaths), that is, a feudal, dynastic thread,2. major feasts of the Catholic church, that is, the ecclesiastical thread (major feasts, anniversaries of priests/bishops, papal election)3. anniversaries of the events of 1848/49, commemorations linked to outstanding Hungarian figures, that is, the Hungarian national, bourgeois national idea.The three threads coexisted peacefully. The parish priest invited to the memorial masses the municipal/local authority, the state bodies, from the 1890s and to certain events also the civil associations. The established order of feasts was the following:- 30th March: “high masses for the defenders of the homeland” (at this date from 1868, before that in November)- 11th April: anniversary of the adoption of the laws of 1848, national feast - Easter, movable feast- 8th August: birthday of the king, Francis Joseph- 10th September: memorial day of the murder of Queen Elisabeth (from 1899)- 4th October: name day of the king, Francis Joseph- 6th October: Arad martyrs- November: “high masses for the defenders of the homeland” (in 1868 transferred from 30th March to this date)- 2nd December: anniversary of the coronation- 25th-26th December: Christmas.The structure of feasts thus combined the feudal, the patriotic national and the ecclesiastical principles of the organisation of feasts, blending the traditional and new rites. The study examines these and their embeddedness in local society.
Keywords: Bölcsészettudományok; Filozófia, etika és vallástudományok